2017
DOI: 10.1002/pros.23437
|View full text |Cite
|
Sign up to set email alerts
|

The 22Rv1 prostate cancer cell line carries mixed genetic ancestry: Implications for prostate cancer health disparities research using pre‐clinical models

Abstract: BACKGROUND Understanding how biological factors contribute to prostate cancer (PCa) health disparities requires mechanistic functional analysis of specific genes or pathways in pre-clinical cellular and animal models of this malignancy. The 22Rv1 human prostatic carcinoma cell line was originally derived from the parental CWR22R cell line. Although 22Rv1 has been well characterized and used in numerous mechanistic studies, no racial identifier has ever been disclosed for this cell line. In accordance with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 64 publications
(145 reference statements)
1
21
0
Order By: Relevance
“…Prostate cancer cell lines are notable for having entirely European ancestry in our data set, despite prostate cancer being the most common cancer among all men and having an estimated incidence rate that is 70% higher among men of African ancestry than it is among men of European ancestry . This is concordant with recent results from Woods‐Burnham and colleagues, who identified substantial African ancestry in a commercially available prostate cancer cell line with previously unknown ancestry, and noted the lack of racial diversity in commercially available prostate cancer cell lines . In esophageal cancer, which is less common among males of African ancestry than among those of European ancestry but significantly more common among females of African ancestry than among those of European ancestry, cell lines demonstrate a similar dearth of African genomic ancestry.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Prostate cancer cell lines are notable for having entirely European ancestry in our data set, despite prostate cancer being the most common cancer among all men and having an estimated incidence rate that is 70% higher among men of African ancestry than it is among men of European ancestry . This is concordant with recent results from Woods‐Burnham and colleagues, who identified substantial African ancestry in a commercially available prostate cancer cell line with previously unknown ancestry, and noted the lack of racial diversity in commercially available prostate cancer cell lines . In esophageal cancer, which is less common among males of African ancestry than among those of European ancestry but significantly more common among females of African ancestry than among those of European ancestry, cell lines demonstrate a similar dearth of African genomic ancestry.…”
Section: Resultssupporting
confidence: 88%
“…41 This is concordant with recent results from Woods-Burnham and colleagues, who identified substantial African ancestry in a commercially available prostate cancer cell line with previously unknown ancestry, and noted the lack of racial diversity in commercially available prostate cancer cell lines. 7 In esophageal cancer, which is less common among males of African ancestry than among those of European ancestry but significantly more common among females of African ancestry than among those of European ancestry, 41 cell lines demonstrate a similar dearth of African genomic ancestry. Although endometrial cancer is more common and more severe among individuals of African ancestry, and has distinct molecular alterations in these individuals, [9][10][11][13][14][15] no endometrial cancer cell lines from our data set have any African ancestry.…”
Section: Tissue-specific Imbalances In Ancestral Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…RON is an RTK, also known as macrophage stimulating‐1 receptor (MST1R) shares structural similarities with c‐MET . Based on the recent report that castrate‐resistant PCa cell line 22Rv1 is of 41% of West African origin and 42% European in origin, we assessed expression and levels of RON and its homolog c‐MET using real‐time PCR and immunoblot analysis. We found that levels and expression of RON were higher in this cell line compared to LNCaP cells (derived from a Caucasian patient; Figure ).…”
Section: Resultsmentioning
confidence: 99%